The Effect of Natural Essential Oil Depigmenting Agent for Alternative Treatment of Melasma - Linda Julianti Wijayadi; Kelvin Kelvin (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2023)
Melasma, known as a hyperpigmentation disorder, is more common in women of childbearing age with Fitzpatrick IV-VI skin types. Various factors of this disease, namely genetic factors, UV exposure, hormonal, thyroid disease, pregnancy, and drugs. The best treatment for melasma is with 2 – 4% hydroquinone, but because of the side effects, alternative treatments are mostly used for melasma. One of them is with essential oils. Essential oils have been investigated as depigmenting agents because of their anti-tyrosinase potential. In this literature, it is proven that the essential oils of sage (Salvia), hedgenettle / woundwort (Stachys), lavender (Lavandula), tea tree (Melaleuca alternifolia), cinnamon (Cinnamomum), mountain tea (Sideritis), pomelo (Citrus grandis ( L) Osbeck), and kaffir lime (Citrus hystrix DC) are effective against melasma. The purpose of this literature is to discuss the various effects of essential oils that can be used as depigmentation agents in the alternative treatment of melasma.